HKUST-1 as a positive electrode material for supercapattery - Azman, Nur Hawa Nabilah; Alias, Muhammad Mustaqhim; Sulaiman, Yusran (Multidisciplinary Digital Publishing Institute, 2023)
The copper-based metal-organic framework (HKUST-1) exhibits interesting properties, such as high porosity and large specific surface area, which are useful as electrode materials for supercapattery. Herein, the HKUST-1 was synthesized through a facile hydrothermal method and exhibited a typical octahedral structure with a specific surface area of 1015.02 m2 g−1, which was calculated using the Barrett–Joyner–Halenda (BJH) method. From the three-electrode analysis, the HKUST-1 demonstrated a specific capacity of 126.2 C g−1 in 1 M LiOH. The structural fingerprint of the HKUST-1 was confirmed with Fourier-transform infrared spectroscopy, Raman spectroscopy, and X-ray diffraction spectroscopy. A supercapattery device, i.e., the HKUST-1//N-doped graphene, revealed a maximum specific power of 300 W kg−1 and a specific energy of 2.61 W h kg−1 at 1 A g−1 with 57% capacitance retention during continuous charging–discharging, even after 10,000 cycles. The HKUST-1 also demonstrated a low charge transfer resistance and a low equivalent series resistance of 7.86 Ω and 0.87 Ω, respectively, verifying its good conductivity. The prominent supercapattery performance of the HKUST-1//N-doped graphene suggested that the HKUST-1 is a promising positive electrode for supercapattery.